Potential applications of solar refrigeration systems for permafrost cooling in embankment engineering - Tian-fei Hu; Zu-run Yue (Case Studies in Thermal Engineering, 2021)
This paper presents the results of an evaluation of two solar-assisted refrigeration systems in protecting permafrost foundations in railway and roadway engineering. A technical comparison was conducted between two types of traditional permafrost cooling measures and refrigeration systems: vapor compression and heat-driven adsorption. The investigated refrigeration systems have better real-time performance and effectiveness than traditional passive heat regulation measures. Moreover, the permafrost regions in China have good potential for solar energy, addressing the issue of decentralized power supply for refrigeration. Two special permafrost cooling systems were designed, manufactured, and tested; the solar photovoltaic vapor compression refrigeration system (SPV-VCRS) and the solar photothermal adsorption refrigeration system (SPT-ARS). The SPV-VCRS prototype exhibits greater potential for permafrost protection, with a consecutive average temperature of −23.55 °C and a coefficient of performance (COP) of 0.41 in the warm season. The SPT-ARS prototype is characterized by an intermittent refrigeration temperature of −1.83 °C and a significantly lower COP of 0.054 per day. Based on the results, suggestions have been given for the selection of solar refrigeration systems for application in the protection of the permafrost under embankments.